2014
DOI: 10.1371/journal.pone.0085983
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Metal-Specific T Cells in Inflamed Skin in a Novel Murine Model of Chromium-Induced Allergic Contact Dermatitis

Abstract: Chromium (Cr) causes delayed-type hypersensitivity reactions possibly mediated by accumulating T cells into allergic inflamed skin, which are called irritants or allergic contact dermatitis. However, accumulating T cells during development of metal allergy are poorly characterized because a suitable animal model is not available. This study aimed to elucidate the skewing of T-cell receptor (TCR) repertoire and cytokine profiles in accumulated T cells in inflamed skin during elucidation of Cr allergy. A novel m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 50 publications
2
18
0
Order By: Relevance
“…Yet, other studies comparing multiple metal allergens – including nickel, cobalt and palladium – have reported a close correlation between skin reactivity and the expression of Th2 cytokines in ACD, and found metal allergens to induce a mixed Th1/Th2 response (Figure c). In a recently published novel mouse model of CHS to chromium, which required co‐application of LPS during sensitization, there was a similar Th2‐dominated response towards chromium . However, in light of the above‐mentioned CHS results with MHC II‐deficient mice, the observed correlation of metal reactivity and Th2 polarization may also reflect a proportional counter response to Tc1/Th1 induction (Figure ) as suggested by the coinduction of IL‐10 by those cells shown to inhibit Th1 cytokine expression without affecting Th2 cytokine production .…”
Section: Metal‐induced Adaptive Immune Responsementioning
confidence: 97%
“…Yet, other studies comparing multiple metal allergens – including nickel, cobalt and palladium – have reported a close correlation between skin reactivity and the expression of Th2 cytokines in ACD, and found metal allergens to induce a mixed Th1/Th2 response (Figure c). In a recently published novel mouse model of CHS to chromium, which required co‐application of LPS during sensitization, there was a similar Th2‐dominated response towards chromium . However, in light of the above‐mentioned CHS results with MHC II‐deficient mice, the observed correlation of metal reactivity and Th2 polarization may also reflect a proportional counter response to Tc1/Th1 induction (Figure ) as suggested by the coinduction of IL‐10 by those cells shown to inhibit Th1 cytokine expression without affecting Th2 cytokine production .…”
Section: Metal‐induced Adaptive Immune Responsementioning
confidence: 97%
“…Based on these previous reports, our novel murine models of allergies against metals such as Pd, Ni, and Cr were induced through sensitization by administration of metal chlorides and LPS into the mouse groin followed by challenge with several kinds of metal chlorides in the footpad of mice [ 8 , 9 , 10 ]. In our metal allergic mouse models, we found significant differences between ICD and ACD.…”
Section: Establishment Of Murine Models For Metal Allergymentioning
confidence: 99%
“…The footpad swelling was reduced at seven days after challenge in ICD mice. However, the footpad swelling continued for 14 days after challenge in ACD mice [ 10 ]. We found that both types of contact dermatitis could not be differentiated by the macroscopic appearance because footpad swelling was the same in both mouse models at one day after challenge.…”
Section: Establishment Of Murine Models For Metal Allergymentioning
confidence: 99%
“…The expression levels of immune response-related genes, including T cell-related CD antigens, cytokines, and cytotoxic granules, were measured by qPCR using the Bio-Rad CFX96 system (Bio-Rad, Hercules, CA, USA). Specific primers for GAPDH, CD3, CD4, CD8, CD14, CD80, IL-1β, IFN-γ, TNF-α, IL-4, IL-5, IL-12, and HDC have been described previously [ 7 , 49 , 50 ]. Freshly isolated total RNA from the footpads of mice was converted to complementary DNA (cDNA).…”
Section: Methodsmentioning
confidence: 99%
“…Adverse skin reactions to metal ions, such as intractable dermatitis, pustulosis palmaris et plantaris, and incompatibility reactions to metal-containing biomaterials are serious problems [ 2 , 3 , 4 ]. It has been suggested that metal allergy is associated with the infiltration of lymphocytes into sites of allergic inflammation [ 5 , 6 , 7 , 8 ]. Among metals in biomaterials, palladium (Pd), which is frequently used in industry, jewelry, surgical instruments, dental implants [ 9 ], and dental materials (it is a common constituent of dental restorative alloys for crowns and bridges) [ 10 , 11 ], causes metal allergy [ 12 ].…”
Section: Introductionmentioning
confidence: 99%